Intra-fractional patient setup error during fractionated intracranial stereotactic irradiation treatment of patients wearing medical masks: comparison with and without bite block during COVID-19 pandemic. (12th November 2020) - Ohira, Shingo; Kanayama, Naoyuki; Komiyama, Riho; Ikawa, Toshiki; Toratani, Masayasu; Ueda, Yoshihiro; Washio, Hayate; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Abstract: The immobilization of patients with a bite block (BB) carries the risk of interpersonal infection, particularly in the context of pandemics such as COVID-19. Here, we compared the intra-fractional patient setup error (intra-SE) with and without a BB during fractionated intracranial stereotactic irradiation (STI). Fifteen patients with brain metastases were immobilized using a BB without a medical mask, while 15 patients were immobilized without using a BB and with a medical mask. The intra-SEs in six directions (anterior–posterior (AP), superior–inferior (SI), left–right (LR), pitch, roll, and yaw) were calculated by using cone-beam computed tomography images acquired before and after the treatments. We analyzed a total of 53 and 67 treatment sessions for the with- and without-BB groups, respectively. A comparable absolute mean translational and rotational intra-SE was observed ( P > 0.05) in the AP (0.19 vs 0.23 mm with- and without-BB, respectively), SI (0.30 vs 0.29 mm), LR (0.20 vs 0.29 mm), pitch (0.18 vs 0.27°), roll (0.23 vs 0.23°) and yaw (0.27 vs 22°) directions. The resultant planning target volume (PTV) margin to compensate for intra-SE was <1 mm. No statistically significant correlation was observed between the intra-SE and treatment times. A PTV margin of <1 mm was achieved even when patients were immobilized without a BB during STI dose delivery.